THE INFLUENCE OF ISLAMIC CORPORATE GOVERNANCE (ICG) AND INTELLECTUAL CAPITAL (IC) ON THE ISLAMICITY PERFORMANCE INDEX AT PT BANK NTB SYARIAH PERIOD 2019-2021 - Sumartiningrum; Muh. Salahuddin (UIN Mataram, 2022)
Islamic bank has different characteristics from other companies in its performance orientation, including PT. Bank NTB Syariah which has converted on September 24, 2018. Islamic banking is required to work in accordance with Islamic business principles and ethics, one of which is through the implementation of governance (Islamic Corporate Governance/ICG) and the use of capital (Intellectual Capital/IC) so that can achieve the goal of establishing a sharia bank that is in accordance with Maqashid Sharia (measured through the Islamicity Performance Index). This study aims to (1) analyze the effect of Islamic Corporate Governance (ICG) disclosure on the Islamicity Performance Index and (2) analyze the influence of Intellectual Capital (IC) on the Islamicity Performance Index and (3) analyze the influence of Islamic Corporate Governance (ICG) and Intellectual Capital. (IC) on the Islamicity Performance Index at PT. Bank NTB Syariah for the 2019-2021 period. The data was secondary data obtained from the financial report. The results showed that Islamic Corporate Governance has a significant effect with a t-statistic value of 21.877 > t-table 1.960, Intellectual Capital has a significant effect with a t-statistic value of 5.642 > t-table 1.960 and Islamic Corporate Governance together with Intellectual Capital has a significant effect on Islamicity Performance Index PT. Bank NTB Syariah from 2019 to 2021 with a t-statistic value of 20.063 > t-table 1.960.